Cogeneration for small users: case studies for Brazilian tertiary sector - Silveira, Jose Luz [UNESP]; da Silva Walter, Arnaldo Cesar [UNESP]; Luengo, Carlos Alberto [UNESP] (My University, 1995)
In this paper we present technical and economic studies of cogeneration systems utilizing combustion engines and gas turbines, applied in two establishments of the tertiary sector, regarding Brazilian conditions (according to Silveria, 1994). In the first step cogeneration systems utilizing combustion engines associated to absorption refrigeration systems are studied, in which electricity and cold air for a university building rate produced. In the second step some possibilities of the use of the gas turbine in cogeneration systems for a hospital are shown. In this case, the exhaust gases are utilized for the production of steam in a heat recovery steam generator (HRSG) or cold water in an absorption refrigeration system (for air conditioning) for the hospital building. The dynamic increment of the energy demand of Brazilian tertiary sector in last years can increase the installation of these cogeneration system (in compact version) as well as strengthen the development of the decentralized energy generation in Brazil.
Keywords: Buildings; Energy utilization; Gas turbines; Hospitals; Industrial economics; Internal combustion engines; Refrigeration; Steam generators; Absorption refrigeration system; Energy generation; Thermal energy; Cogeneration plants